2019
DOI: 10.1002/hep.30514
|View full text |Cite
|
Sign up to set email alerts
|

Direct Inhibition of Hepatitis B e Antigen by Core Protein Allosteric Modulator

Abstract: Hepatitis B e antigen (HBeAg) is an important immunomodulator for promoting host immune tolerance during chronic hepatitis B (CHB) infection. In patients with CHB, HBeAg loss and seroconversion represent partial immune control of CHB infection and are regarded as valuable endpoints. However, the current approved treatments have only a limited efficacy in achieving HBeAg seroconversion in HBeAg‐positive patients. Hepatitis B virus (HBV) core protein has been recognized as an attractive antiviral target, and two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…Cell fractionation and pSTAT1/2 detection in cytoplasmic and nuclear fractions were conducted as described for panel C. p22 shares the exact same amino acid sequence as the core protein except for a 10-aa N-terminal extension, it fails to form a capsid-like structure and support HBV DNA replication ( Fig. 2A), which is consistent with previous studies showing that precore is not required for HBV infection in vivo or replication in vitro (58,59), though it can form heterocapsid with core protein (60,61). It has been shown that the presence of a cysteine at the Ϫ7 position in the N-terminal precore domain of HBeAg causes a preference for the formation of an intramolecular disulfide bond between the Ϫ7 and 61 cysteines over an intermolecular disulfide bond, as seen in the case of the core protein, resulting in HBeAg dimerization in an inverted orientation relative to the core dimer and, thus, precluding capsid formation from HBeAg.…”
Section: Discussionsupporting
confidence: 87%
“…Cell fractionation and pSTAT1/2 detection in cytoplasmic and nuclear fractions were conducted as described for panel C. p22 shares the exact same amino acid sequence as the core protein except for a 10-aa N-terminal extension, it fails to form a capsid-like structure and support HBV DNA replication ( Fig. 2A), which is consistent with previous studies showing that precore is not required for HBV infection in vivo or replication in vitro (58,59), though it can form heterocapsid with core protein (60,61). It has been shown that the presence of a cysteine at the Ϫ7 position in the N-terminal precore domain of HBeAg causes a preference for the formation of an intramolecular disulfide bond between the Ϫ7 and 61 cysteines over an intermolecular disulfide bond, as seen in the case of the core protein, resulting in HBeAg dimerization in an inverted orientation relative to the core dimer and, thus, precluding capsid formation from HBeAg.…”
Section: Discussionsupporting
confidence: 87%
“…Interestingly, studies in multiple in vitro and in vivo HBV experimental models have found that the type I core inhibitor HAP_R01 reduced HBV DNA and HBeAg levels through causing misassembly of its 22 kDa precore protein precursor [ 61 ]. It seems that HAP_R01, as well as other similar CpAMs, have the potential to achieve higher anti-HBe seroconversion rates than the currently approved therapies for patients with CHB.…”
Section: Direct Acting Antiviralsmentioning
confidence: 99%
“…HAP_R01 is a novel HAP-type CpAM (Fig. 1A) that binds to the core protein dimer-dimer interface and effectively inhibits HBV replication and HBeAg biosynthesis in HBVreplicating hepatoma cells (14)(15)(16).…”
mentioning
confidence: 99%